Body Adiposity Index: Its Relevance and Validity in Assessing Body Fatness of Adults. (22nd January 2014) - Gupta, Shilpi; Kapoor, Satwanti
Abstract : Background . One of the limitations of body mass index is its accuracy to assess body fatness. To address this limitation, a new index, body adiposity index, has been developed. However its validity needs to ascertained. Objective . Our aim was to investigate sex-specific relationship between BAI, BMI, and percent body fat in an endogamous population of Delhi, India. Method . Data was collected from 578 adults on bodyweight, height, skinfold thicknesses, hip circumference, waist circumference, and systolic and diastolic blood pressure. Pearson's correlations were calculated for BAI and BMI with PBF. Differences in the correlation coefficients were examined using Fisher'sz tests. Receiver operating characteristic analysis was used to compare the predictive validity and to determine optimal cut-off values. Odds ratios were calculated to assess the risk of having hypertension using the proposed cut-off points. Results . The correlations of PBF with BMI (men:r = 0.83 ; women:r = 0.71 ) were stronger than those with BAI (men:r = 0.66 ; women:r = 0.58 ). In men, the sensitivity and specificity of BAI to predict hypertension were higher than other anthropometric markers but lower than BMI. In women, the sensitivity of BAI was higher than BMI and WC. Conclusions . BAI can be used as an additional marker for screening population; however its validity needs to be demonstrated on other populations too.